The significance of heat transfer through natural convection in stagnation point flow of prandtl fluid - Salman Zeb; Zakir Ullah; A.B. Albidah; Ilyas Khan; Waqar A. Khan (Results in Physics)
This study investigates the stagnation point flow of Prandtl fluid along a stretching sheet in a permeable medium, incorporating natural convection, magnetic field effects, heat generation, thermal radiation, and Soret and Dufour phenomena. The analysis integrates velocity, concentration slips, and temperature jumps within a nonlinear partial differential equation framework. These equations are converted into nonlinear partial differential equations using appropriate dimensionless variables. The key findings reveal that porosity significantly enhances the skin friction coefficient while increasing heat source parameters reduces the Nusselt number. Additionally, chemical reaction parameters markedly elevate concentration distribution. The practical applications of this research include optimizing industrial processes like heat exchangers, cooling systems, and material manufacturing by understanding how permeability and porosity impact heat and mass transfer rates. This study quantifies how magnetic fields can reduce fluid velocity in boundary layers, providing insights for designing energy-efficient systems. These results emphasize the potential to enhance thermal management and operational efficiency in diverse engineering systems.